2015
DOI: 10.1016/j.pce.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in animal activity prior to a major (M= 7) earthquake in the Peruvian Andes

Abstract: During earthquake preparation geophysical processes occur over varying temporal and spatial scales, some leaving their mark on the surface environment, on various biota, and even affecting the ionosphere. Reports on pre-seismic changes in animal behaviour have been greeted with scepticism by the scientific community due to the necessarily anecdotal nature of much of the evidence and a lack of consensus over possible causal mechanisms. Here we present records of changes in the abundance of mammals and birds obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
14
1
3
Order By: Relevance
“…However, in complete contradiction with those synchronous temporal evolutions of abnormal animal behavior and ionospheric perturbations in the above two case studies [25] [35], Figure 3 as our summary for the precursory phenomena for the 2013 Kobe EQ, indicate a completely different view on the correlations of the abnormal animal behavior with corresponding electromagnetic signatures. Hayakawa (2013) [37] presented a hypothesis of the possible seismogenic ULF/ELF radiation as the agent for abnormal animal behavior based on the extensive comparison of the characteristics of abnormal animal behavior by Rikitake [2] with those of different electromagnetic phenomena so far reported [3]- [6].…”
Section: Discussion On Possible Sensory Mechanism Of Abnormal Animal contrasting
confidence: 85%
See 1 more Smart Citation
“…However, in complete contradiction with those synchronous temporal evolutions of abnormal animal behavior and ionospheric perturbations in the above two case studies [25] [35], Figure 3 as our summary for the precursory phenomena for the 2013 Kobe EQ, indicate a completely different view on the correlations of the abnormal animal behavior with corresponding electromagnetic signatures. Hayakawa (2013) [37] presented a hypothesis of the possible seismogenic ULF/ELF radiation as the agent for abnormal animal behavior based on the extensive comparison of the characteristics of abnormal animal behavior by Rikitake [2] with those of different electromagnetic phenomena so far reported [3]- [6].…”
Section: Discussion On Possible Sensory Mechanism Of Abnormal Animal contrasting
confidence: 85%
“…Further they have indicated that these days were coincident with those of ionospheric perturbations as detected by subionospheric VLF/LF propagation by Hayakawa et al [32]- [34], without commenting on a possible mechanism of abnormal animal behavior. Another interesting paper has been published recently by Grant et al (2015) [35], who have shown the unusual behavior of animals in the national park prior to a major (M = 7) EQ in the Peruvian Andes, and this abnormal animal behavior was coincident in time with the dates of ionospheric perturbation by the VLF propagation anomalies. Then, they have proposed a possible agent for both the abnormal animal behavior and ionospheric perturbation by a common effect of air ionization due to the pre-EQ generation of positive hole carriers [36].…”
Section: Comparison With Electromagnetic Precursorsmentioning
confidence: 97%
“…Most famously, the 1975 Haicheng earthquake (magnitude M 7.2) in China, was anticipated based on human observations of animal behavior, such as snakes or rats leaving their burrows in winter [13]. Similar observations are rare [14], but recently evidence accumulated that animals in earthquake areas may show aberrant behavior [15][16][17][18][19][20][21][22]. Nevertheless, a recent review [23] points out the sparsity of data and need for testable quantitative measures on animal-anticipated earthquake occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this hypothesis, observations of daily cow milk yields and ULF radiation from the same period in the same region need to be performed. There is an interesting report that discussed possible mechanisms for UAB prior to earthquakes based on observational data [22]. This study shows that the amount of wildlife (i.e., mammals and birds) captured by motion-triggered cameras in a national park decreased prior to the Contamana earthquake (M = 7.0) in the Peruvian Andes, and the lag time between these behavioral changes and the earthquake was coincident with the VLF propagation anomalies.…”
Section: Discussionmentioning
confidence: 70%
“…As an example of quantitative UAB, changes in the locomotive activities of mice before large earthquakes were reported by Yokoi et al [20] and Li et al [21]. Grant et al [22] recently revealed, by the use of motion-triggered cameras, that wild animal activity in various species declined prior to the Contamana earthquake, with a magnitude (M) of 7.0. However, these reports were case studies for single large earthquakes.…”
Section: Introductionmentioning
confidence: 96%